240 Beef Heifers with Increased Number of Follicles Have Greater Uterine Luminal Glucose Concentrations. (8th October 2021) - Snider, Alexandria; Crouse, Matthew S; Rosasco, Shelby; Epperson, Kaitlin M; Northrop-Albrecht, Emmalee J; Rich, Jerica J; Chase, Chad; Miles, Jeremy R; Summers, Adam; Cushman, Robert A
Abstract: Increased numbers of antral follicles are associated with greater fertility and a uterine environment that is more supportive of early embryonic development in beef heifers. Glucose is a primary energy source for embryos and glucose concentrations are elevated in uterine luminal fluid (ULF) of pregnant heifers. We hypothesized that ULF glucose concentrations and endometrial transcript abundance for glucose transporters at d16 after insemination would be greater in heifers with increased numbers of antral follicles. Heifers classified with either increased (32 ± 1.1) or diminished (14.7 ± 1.1) antral follicle counts were selected and artificially inseminated following the Select Synch protocol (d0). At d16 after insemination, heifers were sent to the abattoir and reproductive tracts were collected to retrieve conceptuses to determine pregnancy. Uterine luminal fluid was collected, the endometrium was biopsied, total RNA was extracted and glucose transporter transcript abundance was determined. Data were analyzed using the MIXED procedure of SAS with antral follicle group, pregnancy status, and the interaction as fixed effects. Glucose concentrations in ULF were greater (P < 0.05) in heifers with increased antral follicle numbers compared to heifers with diminished numbers (122.65 ± 11.91 vs 84.12 ± 12.42 mg/dL). Glucose ULF concentrations were increased (P < 0.05) in pregnant vs. non-pregnant heifers (124.84 ± 12.81 vs 81.93 ± 11.50 mg/dL). Endometrial glucose transporter 1 (GLUT1) transcript abundance was increased in pregnant heifers (P < 0.01) but was not different due to antral follicle number or the interaction. Therefore, differences in glucose concentrations associated with antral follicle number may be due to differences in GLUT1 transcription before d16 or due to differences in protein abundance or functionality. Taken together, heifers with increased number of antral follicles may have increased energy availability in the uterus for trophoblast proliferation and function. USDA is an equal opportunity provider and employer.